2005
DOI: 10.1002/jsfa.2155
|View full text |Cite
|
Sign up to set email alerts
|

Performance, carcass cut‐up and fatty acids deposition in broilers fed different levels of pellet‐processed flaxseed

Abstract: The effects of flaxseed (FS) processing and inclusion levels on broiler performance and fatty acid deposition were examined. FS was provided as whole seed, ground or pellet-then-mashed at a dietary level of 0, 12 or 14% during days 1 to 21. These levels represented control, threshold and over-threshold, respectively. During days 22 to 40, the threshold level was increased to 15%, while the over-threshold level increased to 17%. After 21 days of feeding, the performance of birds fed a diet with 12% pellet-then-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 21 publications
4
9
0
Order By: Relevance
“…Many studies have demonstrated the close relationship between the flavour preference of chicken and overall acceptance [19,20]. This study confirms the finding of [21,22] that flavour of chicken depends on breed, and cut of meat. Even though Tshabalala et al [23] found no significant difference between broiler and IC for the specific sensory attributes of interest, it must be borne in mind that their study was based on same age for both broiler and Ethiopian IC.…”
Section: Flavour/aromasupporting
confidence: 89%
“…Many studies have demonstrated the close relationship between the flavour preference of chicken and overall acceptance [19,20]. This study confirms the finding of [21,22] that flavour of chicken depends on breed, and cut of meat. Even though Tshabalala et al [23] found no significant difference between broiler and IC for the specific sensory attributes of interest, it must be borne in mind that their study was based on same age for both broiler and Ethiopian IC.…”
Section: Flavour/aromasupporting
confidence: 89%
“…Bond et al (1997) concluded that flaxseed was not a practical oil source, as more than 10% of flaxseed in the diet caused a significant performance reduction. Shen et al (2005) also observed lower weight gain and poor feed conversion efficiency in the birds fed with flaxseed supplemented diet as compared to canola or extruded full-fat soybean-based diets. Moreover, poor performance of birds fed with flaxseed-based diets may also be due to the presence of anti-nutritional factor such as linatine.…”
Section: Growth Performancementioning
confidence: 80%
“…Different levels of flaxseed in the diet also reduced the LA in meat samples. Other studies had (Ajuyah et al 1993;Shen et al 2005;Betti et al 2009;Rahimi et al 2011) also reported that the response of tissue fatty acid profiles to dietary flaxseed inclusion follows a proportional pattern that reflects dosage and period of dietary flaxseed treatment.…”
Section: Carcass Yield and Qualitymentioning
confidence: 96%
“…The dietary use of flaxseed has been proposed by many authors to obtain meat with raised n-3 PUFA in beef cattle (Scollan et al, 2001;Raes et al, 2004), in pigs Riley et al, 2000;Matthews et al, 2000) and in chickens (Rymer and Givens, 2005;Shen et al, 2005). The possibility of improving the n-3 PUFA proportion and decreasing the n-6/n-3 ratio of rabbit meat by dietary supplementation has important implications and the inclusion of flaxseed in diets has successfully been attempted in rabbits (Bernardini et al, 1999;Cavani et al, 2003;Dal Bosco et al, 2004;Colin et al, 2005;Bianchi et al, 2006Bianchi et al, , 2009Kouba et al, 2008).…”
Section: Introductionmentioning
confidence: 99%